1987
DOI: 10.1055/s-0038-1646037
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism Leads to More Small-Sized Platelets in Circulation

Abstract: SummaryThe effect of induced hypothyroidism on platelet count and platelet volume distribution was studied in twelve athyreotic patients, After a two weeks withdrawal of triiodothyronine supplementation, platelet count and the ratio between platelet and red cell count were increased in all patients. Furthermore, mean platelet volume was declined and platelet distribution width was risen. Thus, hypothyroidism appears to increase the number of circulating platelets, especially the smaller ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Currently, limited and conflicting data regarding the relationship between thyroid function and MPV have been reported in small-scale case-control studies (17)(18)(19)(20)(21)(22). To our knowledge, no study has been based on a general population, particularly in those who were thought to be healthy and euthyroid.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Currently, limited and conflicting data regarding the relationship between thyroid function and MPV have been reported in small-scale case-control studies (17)(18)(19)(20)(21)(22). To our knowledge, no study has been based on a general population, particularly in those who were thought to be healthy and euthyroid.…”
Section: Introductionmentioning
confidence: 74%
“…Van Doormaal et al (17) found small-sized platelets in overt hypothyroidism, whereas Ford et al (18) did not show smallsized platelets in overt hypothyroidism. Coban et al (19), Erikci et al (20), and Yilamz et al (21) reported an increased MPV in the SCH group compared with the euthyroid states.…”
Section: Kim Et Almentioning
confidence: 97%
“…Use of platelet volume or size to characterize blood disorders allows detection of more subtle changes in thrombocytopoiesis (24) than platelet count alone. Ford et ale (25) have described an increased mean platelet volume in human hyperthryoid patients, and conversely, van Doormal et ale (26) have reported that small-sized platelets predominate in the hypothyroid state.…”
mentioning
confidence: 95%
“…For example, MPV and platelet distribution width bear importance in the discrimination of myeloproliferative diseases, essential thrombocytosis and reactive thrombocytoses (6,7). Many studies on clinical benefit of MPV were made on many subjects such as splenectomy, microcytic anemia, serebral infarct (8-10), thrombocytopenia (11,12), thrombocytoses (6,7), congenital platelet diseases, sepsis, chronic obstructive lungal diseases (13), chronic venous failure (14), high MPV in hyperthyroidism (15), low MPV in hyperthyroidism (16), hypertension and preeclampsia in pregnanacy, organic solvent toxicity.…”
Section: Introductionmentioning
confidence: 99%